Operation for gastro-oesophageal reflux associated with severe mental retardation. Issue 3 (March 1993) - Spitz, L; Roth, K; Kiely, E M; Brereton, R J; Drake, D P; Milla, P J
Abstract : One hundred and seventy six children with severe mental retardation underwent a fundoplication for considerable gastro-oesophageal reflux. There were six 'early' (3%) deaths and five 'late' deaths. Major complications developed in 17 (10%) children whereas 86 (49%) had 'minor' complications. A revision operation was required in 27 patients. Overall 142 (81%) children achieved a good result. In spite of the high complication rate and the need for a secondary operation in 15% of the patients, the quality of life for these children and their parents and carers is greatly improved by antireflux surgery.